2021
DOI: 10.3389/fneur.2021.700115
|View full text |Cite
|
Sign up to set email alerts
|

Melodic Intonation Therapy for Post-stroke Non-fluent Aphasia: Systematic Review and Meta-Analysis

Abstract: Introduction: Melodic intonation therapy (MIT) is one of the most studied speech and language therapy (SLT) approaches for patients with non-fluent aphasia, although the methodological quality of the studies has been rated as low in previous reviews. The aim of this study is to update current evidence on the possible efficacy of MIT for the treatment of non-fluent post-stroke aphasia.Methods: A systematic review and meta-analysis. We selected randomized clinical trials (RCT) that included adult patients over 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
(76 reference statements)
0
13
0
1
Order By: Relevance
“…In contrast, no such influence was identified in individual music therapy for depression, nor did age or musicianship predict significant responses [ 55 ]. Evaluating clinical and neurobiological predictors of treatment response to music therapy after stroke would be of great importance for further improving our understanding of stroke rehabilitation with music-based interventions.In conclusion, our findings suggest that the behavioural gains on language and memory induced by a daily music listening intervention after stroke [ 13 , 14 , 15 ] are associated with greater initial severity of the language/memory deficit, higher education level, and greater baseline music-evoked connectivity in the auditory network and activation in frontoparietal areas. Clinically, this may indicate that especially stroke patients with more severe language and memory deficits, higher cognitive reserve capacity, and greater neural responsiveness to music stimuli could benefit most from daily music listening during the first post-stroke months.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In contrast, no such influence was identified in individual music therapy for depression, nor did age or musicianship predict significant responses [ 55 ]. Evaluating clinical and neurobiological predictors of treatment response to music therapy after stroke would be of great importance for further improving our understanding of stroke rehabilitation with music-based interventions.In conclusion, our findings suggest that the behavioural gains on language and memory induced by a daily music listening intervention after stroke [ 13 , 14 , 15 ] are associated with greater initial severity of the language/memory deficit, higher education level, and greater baseline music-evoked connectivity in the auditory network and activation in frontoparietal areas. Clinically, this may indicate that especially stroke patients with more severe language and memory deficits, higher cognitive reserve capacity, and greater neural responsiveness to music stimuli could benefit most from daily music listening during the first post-stroke months.…”
Section: Discussionmentioning
confidence: 75%
“…During the last 20 years, promising evidence has emerged on the efficacy of music-based interventions targeted for specific cognitive, motor, and verbal deficits caused by stroke [ 1 ]. These include active interventions that utilize instrument playing or musical rhythm to rehabilitate deficits in motor control of movements (hemiparesis) [ 13 ] and singing-based methods to rehabilitate deficits in speech production (aphasia) [ 14 ] as well as receptive interventions that utilize music listening. In three randomized controlled trials (RCTs), daily music listening during the first three post-stroke months has been reported to enhance the recovery of verbal memory, attention, and language skills compared to a control intervention (audiobook listening) or standard care [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have attempted to discern the different neurobiological mechanisms which promote language recovery and neuroplastic reorganization through MIT therapy. First, a recent review demonstrated its effectiveness in language improvement [ 11 ]. Second, in other reviews, the different neurobiological and cognitive mechanisms of MIT were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…13 So far, there have been several systematic reviews 14,15 and metaanalyses on MIT. [16][17][18] Existing meta-analyses reflect a relatively limited amount of RCT data, 16 dichotomize posttreatment improvement in a way that prevents specific effect size estimates, 17 or do not operationalize quality of outcomes (psychometrically validated vs. unvalidated tests), experimental design (presence vs. absence of randomization and control group), influence of spontaneous recovery (quantified as number of months post-stroke), MIT protocol applied (original vs. modified), and level of generalization (performance on trained vs. untrained items). 18 Given the substantial burden of disease associated with aphasia, the current meta-analysis attempts to provide a deeper understanding regarding the clinical potential and possible limitations of MIT.…”
Section: Introductionmentioning
confidence: 99%